Digital Marketing Suggestions for Luxury Brands - Eru, Oya (European Journal of Multidisciplinary Studies, 2018)
Nowadays, consumption is not an activity made for only to meet basic consumer needs. It is believed that, some of the purchased products or brands reflect the lifestyle, the style, trend or the status of consumers'. These products or brands can define as lux products or brands. Also, the perception of the haute couture products as symbols of status or power, and the economic developments in the world, increase the interest and the demand for lux products or brands too. Luxury can be described as a lifestyle. After democratization, luxury brands start to be more accessible and start to create lover cost designs and distribution channels. Given these circumstances, it can be said that democratization of luxury can be described as a revolution in luxury sector. So, starting from this point, it can be said that, some one can perceive luxury as equal to rarity or some one perceive luxury as quality, special, prestigious or something like else. Another revolution in luxury industry can be called as digital revolution. Although there are traditional marketing applications for luxury brands, brands should not to ignore that new media channels have emerged. These channels can be described as internet and social media. At the present time, the internet is using in every place and every area of our lives and it is also using as a new shopping environment. And consumers start to use the internet and social media as a new shopping tool intensively too. So luxury brands have to recognize that they start to take place in the internet and social media according to the situations mentioned above. Using the internet and social media as a shopping channel provides a number of advantages to producers, brands and consumers. These advantages can be listed as follows; Internet and social media provide brands, producers and consumers to establish an interactive communication with each other. Internet and social media, help customers to participate in the development process of products.Customers' ideas and experiences about brands and products can be measured faster Thanks to the Internet and social media.Thanks to the Internet and social media, people beyond the country's borders can exchange ideas with each other and have an opportunity to be able to follow brands they want.In addition, accessing the products from anywhere anytime, reducing costs and opportunities to build customer databases can be counted as the benefits of internet and social media too.Judging from the advantages mentioned above, in order to adapt to today's conditions, it can be said that, the luxury brands have to develop digital strategies by necessity. Also to reach generation z, who are the potential customers of the future, it can be mentioned that, luxury brands need to improve digital strategies too. In addition, when people searching luxury goods on the internet, for not to encounter counterfeit products, it is important that luxury brands should make their own online environments, such as social media accounts or websites.To attract consumers’ attention, luxury brands can create innovative campaigns over social media. Besides, creating an online magazine, creating mobile applications or mobile games include adwergames can be beneficial for luxury brands. Also, creating vblogs or using celebrities or celebrity bloggers can be useful for luxury brands. Especially luxury brands in beauty industry can create innovative mobile apps and games.
Keywords: Luxury Brands, Internet, Social Media.